Dysfunction of Olfactory System [Working Title] 2019
DOI: 10.5772/intechopen.90116
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modality Dysfunction between the Visual and Olfactory Systems in Parkinson’s Disease

Abstract: Cross-modality in function is a fundamental ability in humans and is closely associated with the basic functions. Several studies have demonstrated that vision strongly influences other senses such as hearing, touch, taste, and smell. However, the dysfunction in this cross-modality caused by disease, is poorly understood. In addition to evidence that Parkinson's disease (PD) impairs various cognitive functions including olfaction, a recent study showed that olfactory function is unaffected by visual informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Odor‐color cross‐modal correspondences have been reported in many studies (Goubet et al, 2018; Kemp & Gilbert, 1997; Levitan et al, 2014; Luisa Demattè et al, 2006; Motoyasu, 2020; Speed et al, 2021; Spence, 2020). Speed et al (2021) found that odors were matched with their corresponding colors after age of 10 and Goubet et al (2018) reported the same phenomenon as early as 6 years of age.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Odor‐color cross‐modal correspondences have been reported in many studies (Goubet et al, 2018; Kemp & Gilbert, 1997; Levitan et al, 2014; Luisa Demattè et al, 2006; Motoyasu, 2020; Speed et al, 2021; Spence, 2020). Speed et al (2021) found that odors were matched with their corresponding colors after age of 10 and Goubet et al (2018) reported the same phenomenon as early as 6 years of age.…”
Section: Discussionmentioning
confidence: 86%
“…Odor-color cross-modal correspondences have been reported in many studies (Goubet et al, 2018;Kemp & Gilbert, 1997;Levitan et al, 2014;Luisa Demattè et al, 2006;Motoyasu, 2020;Speed et al, 2021;Spence, 2020). 2.…”
Section: Discussionmentioning
confidence: 89%